The Fulfilment Of The Right To Health Services Through Control Of Ombudsman Functions In The Region - Agus Triono (Bandar Lampung University, 2015)
The right to good health care is a basic right of citizens guaranteed by the constitution that must be fulfilled. But the vagueness of the benchmarks of public services and the effectiveness of oversight institutions become an obstacle in fulfilling the right to health services, especially in the era of regional autonomy by implementing decentralization of authority to the regions in health. Therefore, in this study discussed on how the right to health services through the oversight function of the Ombudsman in the area and whether barriers.Based on research conducted using normative legal research methods using statutory approach and conceptual approach as well as social-legal mind that the right to health care is an obligation of the state in efforts to implement human rights norms that honor to respect, to protect and to fulfil and must meet the principles, among others, the availability of health services, accessibility, acceptability and quality. In the context of regional autonomy, decentralization in the health sector to the region has given local authorities organize public services, although in practice, there are still many areas which were not optimal in the rain due to differences in the ability of the financial implications for the implementation of public service which is not in accordance with prescribed standards. The presence of the Ombudsman to be important even though there are various barriers internally, among others related to statutory provisions that have not been given the strengthening of the Ombudsman institution in the state system, the binding force of law issued by the Ombudsman products is only morally binding so that execution given the government agency itself has not been fully implemented and the lack of resources and funding sources Ombudsman. While externally the object of supervision, such as government and society in general who do not understand the essence of the establishment of the Ombudsman institution and do not want to run any recommendations of the Ombudsman.